Analysis of the enforcement of the international agreement on social security between Brazil and Italy - Gonzalez, Maria José Jung (Journal of Health Law, 2011)
The present paper approaches the international social security agreement between Brazil and Italy and the importance of this agreement, once it is not well known. Initially, it approaches the international health scene, with a historic of Brazilian and Italian health systems; the agreement exists between the countries and the analysis of the execution by the convenience method. The tendency of the International agreements is the worldwide globalization, ratifying the need of breaking juridical and political obstacles involving a great effort in the migratory treatment. The main goal of this international agreement is to guarantee the social welfare planned in the legislation of the two countries, including intending to create a common legal base regarding the obligations and rights of the beneficiary. Nowadays the benefit system is seen as a security tool and indispensable welfare to meet the needs of stability of the migrant workers, and in this trail, it becomes mandatory its divulgation.